2022
DOI: 10.1111/resp.14382
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal lung function in urban firefighters: A group‐based multi‐trajectory modelling approach

Abstract: Background and Objective: Urban firefighters are routinely exposed to both physical and chemical hazards that can negatively impact lung health, but it is unclear if firefighters experience accelerated decline in spirometry parameters due to chronic exposure and acute insults. This study aimed to describe sub-groups of firefighters with differing spirometry trajectories and examine the relationship between the identified trajectories and demographic, lifestyle and occupational characteristics. Methods: Data fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 43 publications
(100 reference statements)
0
6
0
Order By: Relevance
“…Western Kentucky University (WKU) Center for Environmental and Workplace Health (CEWH) research team previously identified a concern for negative health outcomes with firefighter exposures to work-related toxic substances and behaviors on management of turnout gears (coats and pants) [13][14][15]. Overall, there is limited literature on firefighters' exposure to biological contaminants; most of the previous studies are limited to chemical exposures [14][15][16] and were conducted in urban areas [17][18][19]. Therefore, the purpose of this study was to compare career and volunteer firefighters' knowledge and practice behaviors on infection transmission in the dayroom and during emergency runs.…”
Section: Introductionmentioning
confidence: 99%
“…Western Kentucky University (WKU) Center for Environmental and Workplace Health (CEWH) research team previously identified a concern for negative health outcomes with firefighter exposures to work-related toxic substances and behaviors on management of turnout gears (coats and pants) [13][14][15]. Overall, there is limited literature on firefighters' exposure to biological contaminants; most of the previous studies are limited to chemical exposures [14][15][16] and were conducted in urban areas [17][18][19]. Therefore, the purpose of this study was to compare career and volunteer firefighters' knowledge and practice behaviors on infection transmission in the dayroom and during emergency runs.…”
Section: Introductionmentioning
confidence: 99%
“…In Australia in 2020–2021, there were 17,459 paid firefighters, but many more 144,159 volunteer firefighters 9 . Only 2% of participants in the South Australian study were female 6 . In another cohort study, covering the majority of Australian firefighters (but not South Australia or Tasmania), 4% of full‐time paid, 8% of part‐time paid and 23% of volunteers were women 8 .…”
mentioning
confidence: 96%
“…9 Only 2% of participants in the South Australian study were female. 6 In another cohort study, covering the majority of Australian firefighters (but not South Australia or Tasmania), 4% of full-time paid, 8% of part-time paid and 23% of volunteers were women. 8 Given that women generally have smaller lungs than men and might be more susceptible to the effects of smoke, further research on female firefighters is required.…”
mentioning
confidence: 99%
See 2 more Smart Citations